The Psychological Impacts of a COVID-19 Outbreak on College Students in China: A Longitudinal Study - Hong Yan Li; Hui Cao; Doris Y. P. Leung; Yim Wah Mak (2020)
An outbreak in Wuhan, China in late 2019 of a highly infectious new coronary pneumonia (COVID-19) led to the imposition of countrywide confinement measures from January to March 2020. This is a longitudinal study on changes in the mental health status of a college population before and after their COVID-19 confinement for the first two weeks, focusing on states of psychological distress, depression, anxiety and affectivity. The influence of possible stressors on their mental health were investigated, including inadequate supplies and fears of infection. Five hundred and fifty-five undergraduate students were recruited from Hebei Agricultural University in Baoding, China. The participants completed two online surveys—on anxiety and depression, and on positive and negative affect. One survey was conducted before the confinement and the other was conducted 15–17 days after the start of the confinement. Increases in negative affect and symptoms of anxiety and depression (p-values < 0.001) were observed after 2 weeks of confinement. Inadequate supplies of hand sanitizers, a higher year of study, and higher scores on anxiety and depression were common predictors of increased negative affect, anxiety, and depression across the confinement period. The results suggest that healthcare policymakers should carefully consider the appropriate confinement duration, and ensure adequate supplies of basic infection-control materials.